2016
DOI: 10.3390/children3040023
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of Parenting Magazines Advertisements with American Academy of Pediatrics Recommendations

Abstract: This study examined 3218 advertisements from the two parenting magazines with highest circulation in the United States. The authors compared each advertisement for a product for use by children, against all the published recommendations of the American Academy of Pediatrics (AAP) on topics such as toy safety, helmet use, age-defined choking hazards, infant sleep safety, and others. Any advertisement with images or products which went against a published AAP recommendation was deemed as non-adherence and was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…In recent years there has been an explosion of misinformation, whether willful or not, via search engines, polarized mainstream and social media. Several papers have shown that even on neutral medical topics such as infant sleep position, a large fraction of website information is misleading or wrong (Joyner et al, 2009;Pitt et al, 2016;Moon and Task Force On Sudden Infant Death, 2016). The issues of the post-truth era and its impacts on democracy and policymaking and public understandings and attitudes well documented by others (Davies, 2016;Speed and Mannion, 2017;McIntyre, 2018).…”
Section: Theory Meets Practicementioning
confidence: 99%
“…In recent years there has been an explosion of misinformation, whether willful or not, via search engines, polarized mainstream and social media. Several papers have shown that even on neutral medical topics such as infant sleep position, a large fraction of website information is misleading or wrong (Joyner et al, 2009;Pitt et al, 2016;Moon and Task Force On Sudden Infant Death, 2016). The issues of the post-truth era and its impacts on democracy and policymaking and public understandings and attitudes well documented by others (Davies, 2016;Speed and Mannion, 2017;McIntyre, 2018).…”
Section: Theory Meets Practicementioning
confidence: 99%
“…Anket sorularının doğru cevapları hazırlanırken American Academy of Pediatrics (AAP) (9), American Academy of Pediatric Dentistry (AAPD)(2), American Dental Association (ADA)" nın(10) güncel rehberliğinden yararlanılmıştır.…”
Section: Araştırma Verilerinin Elde Edilmesiunclassified
“…So, they come to a false conclusion that if a product is advertised, it is safe to buy it. Therefore, it is important to educate children to make them recognize what is appropriate for their health and lifestyle (Kline, 2005;Pitt, Berger, & Sheehan, 2016;Reisigg, Strain, & Griffiths, 2009). An appropriate legislative regulation including age limitation is needed to decrease consumption of these kinds of drinks among children and adolescents.…”
Section: Preventive Measuresmentioning
confidence: 99%